2017
DOI: 10.1130/g38608.1
|View full text |Cite
|
Sign up to set email alerts
|

Tidal rhythmites in the southern Bouse Formation as evidence for post-Miocene uplift of the lower Colorado River corridor

Abstract: Uncertainty over depositional paleo environ ments of the upper Miocene to lower Pliocene Bouse Formation obscures our understanding of the timing and magnitude of regional uplift as well as the conditions and processes that were active during integration and early evolution of the Colorado River (western United States). This paper presents new sedimentologic and quantitative evidence for a strong tidal influence on deposition of the basal carbonate member of the southern Bouse Formation. Lithofacies with tidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 28 publications
8
46
0
Order By: Relevance
“…This conclusion is similar to that of previous workers (Buising, 1988(Buising, , 1990Pearthree and House, 2014), though the paleoenvironment of the receiving body of water (lake vs. marine) is debated (e.g. Bright et al, 2016;O'Connell et al, 2017). Broadly channelized cross-bedded sandstone bodies represent terminal distributary channels, and tabular-bedded silt and fine sand accumulated in channel-mouth bars of a low-gradient delta front system (e.g., Olariu and Bhattacharya, 2006;Ahmed et al, 2014).…”
Section: Red Mudstone and Siltstonesupporting
confidence: 79%
See 2 more Smart Citations
“…This conclusion is similar to that of previous workers (Buising, 1988(Buising, , 1990Pearthree and House, 2014), though the paleoenvironment of the receiving body of water (lake vs. marine) is debated (e.g. Bright et al, 2016;O'Connell et al, 2017). Broadly channelized cross-bedded sandstone bodies represent terminal distributary channels, and tabular-bedded silt and fine sand accumulated in channel-mouth bars of a low-gradient delta front system (e.g., Olariu and Bhattacharya, 2006;Ahmed et al, 2014).…”
Section: Red Mudstone and Siltstonesupporting
confidence: 79%
“…Coarse bioclastic facies commonly pass down cross-bed foresets into finer grained heterolithic facies. Based on detailed sedimentologic analysis of sedimentary structures and facies associations, and Fourier transform analysis of layered rhythmites, O'Connell et al (2017) showed that the bioclastic facies association was deposited by tidal currents in a tide-dominated marine setting. This interpretation is corroborated by marine foraminiferal species that record an up-section increase in water depth through the bioclastic unit into the overlying marl (see below).…”
Section: Bioclastic Facies (Tidalites)mentioning
confidence: 99%
See 1 more Smart Citation
“…The fossil record of the lower Bouse Formation includes a bewildering mixture of apparently marine or estuarine (e.g., planktic foraminiferans, barnacles, and Thalassinoides trace fossils) and lacustrine (ostracodes, Chara, molluscs) fossils (Bright et al, 2018b). Sigmoidal bedding and other depositional features interpreted to be of marine tidal origin (O'Connell et al, 2017) were also interpreted by Spencer et al (2018) to indicate a lacustrine origin. Isotopic data (C, O, and Sr) from Bouse carbonates uniformly point towards a continental water source, either similar to or modified from CR water, with little indication of a marine influ-ence (Spencer and Patchett, 1997;Bright et al, 2016Bright et al, , 2018a.…”
Section: Introductionmentioning
confidence: 90%
“…of the modern Great Salt Lake (Utah). For decades, geologists, paleontologists, and geochemists have been embroiled in a scientific debate as to the paleoenvironmental nature and age of these water bodies (e.g., Buising, 1990;Spencer and Patchett, 1997;McDougall, 2008;Spencer et al, 2008Spencer et al, , 2013McDougall and Miranda Martínez, 2014;Gootee et al, 2016;O'Connell et al, 2017;Bright et al, 2018a, b;Dorsey et al, 2018) and the implications of these variable interpretations for the history of the CR, the integration of the river into the evolving Gulf of California, and regional tectonic history, including both the southern basin and range region and the Colorado Plateau (e.g., Bennett et al, 2016;Karlstrom et al, 2017;Pearthree and House, 2014;Crow et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%